The Effect of Scout Extracurricular Activities on the Learning Outcomes of Class X Students in Biology Subjects at State Senior High School 1 Besuki - Sari, Dwi Nur Rikhma (Journal of Natural Sciences and Learning, 2024)
Extracurricular activities are activities of students outside tutoring, extracurricular activities can give effect to their interests, talents and potential of the students. Extracurricular are much in demand by students that scouts, including in SMA Negeri 1 Besuki. Ektrakurikuler conditions scout in SMA Negeri 1 Besuki pretty good because a lot of students who take these activities even for class X are required to follow. But many students are still less know the benefits and purpose of the mandatory extracurricular scout. Based on the description of the background of the problem, this study was formulated as follows: Is there Scouting Against Effects of Extracurricular Activities Student Results Class X By Subject Biology at SMA Negeri 1 Besuki school year of 2014/2015? This type of research that is ex post facto correlational descriptive with quantitative approach. Data collection techniques with the questionnaire method (questionnaire) and documentation. Statistical calculations done using a simple correlation with significant results seen from the value of r count larger than r table at a significance level of 5% ie 0.658> 0.246. Based on the results of research and discussion that has been done, it can be concluded that there is influence of extracurricular activities scouts on learning outcomes of students in the subjects of Biology class X SMA Negeri 1 Besuki school year 2014/2015